تقييم أثر التدريب على أداء العاملين (دراسة ميدانيه على الأدلاء السياحيين الأردنيين ) - ميا علي يونس; العون سالم سفاح; السرحان هايل فلاح (Latakia University Journal - Economic and Legal Sciences Series, 2013)
نظراً لارتباط نمو وتطور النشاط السياحي في أي بلد بمدى توفر العنصر البشري المؤهل والمدرب لتقديم خدمات ذات نوعية وجودة عالية و تلبي وتشبع رغبات السائح سواء كان محلياً أم أجنبياً، فإن هذا الأمر الذي دفع الدول التي تُعد السياحة موردها الاقتصادي الهام إلى الاهتمام بشكل كبير بتأهيل العاملين في قطاع الخدمات السياحية بحيث ارتبط تطورها السياحي بمدى العناية التي توليها بمجال التأهيل والتدريب بقواها البشرية العاملة في المجال السياحي. فقد هدفت هذه الدراسة إلى تقييم أثر التدريب على أداء الأدلاء السياحيين الأردنيين، وذلك بهدف معرفة أثر البرامج التدريبية المقدمة لهم في تحسين أدائهم، ومدى كفاءة هذه البرامج وطرق تصميمها، وكذلك بيان العلاقة بين احتياجات الأدلاء السياحيين الفعلية من التدريب، ومدى ارتباط هذه الاحتياجات مع مهامهم الوظيفية، وكذلك العلاقة بين مهارات وقدرات المدربين والمتدربين وأثرها في الأداء. وقد توصلت الدراسة إلى وجود علاقة ارتباط ذات دلالة معنوية بين التدريب وأداء الأدلاء السياحيين. The growth and development of tourism in any country is related to the availability of qualified and trained human factor in order to provide high quality services that meet and satisfy the domestic or foreign tourists’ desires. This prompted countries that depend on tourism as a significant source of income, and to rehabilitate workers in tourism services. Thus, development of tourism is related to the amount of attention paid to qualifying and training its manpower in tourism. This study aimed to assess the impact of training on the performance of the Jordanian tourist guides in order to determine the impact of training programs in improving their performance and the efficiency of these programs. It also aimed to assess the extent of efficiency of these programs and their designing methods. It also aimed to point out the relationship between the actual requirements of tourist guides of training and the extent of the relationship between these requirements and instructors and learners’ capabilities and their impact on performance. The study revealed that there is a significant correlation between training and tourist guides’ performance.